Highly thermostable Ba2Ln2Ge4O13:Dy3+ (Ln = Y, Gd) phosphors: Synthesis and optical properties - Tang, Huan; Li, Hong; Song, Ruitong; Yang, Zhiqin; Zhao, Rui; Guo, Zewen; Li, Junpeng; Wang, Bo; Zhu, Jing (Ceramics international, 2023)
In this study, the pure powder Ba2Y2Ge4O13 (BYGO) is constructed using the lanthanide substitution of Y for Gd based on Ba2Gd2Ge4O13 (BGGO). The activator Dy3+ ions are solidly dissolved into the BYGO and BGGO hosts via occupying the Y3+ and Gd3+ sites, respectively. Under 352 nm excitation, the similarity and difference of the yellowish-white-emitting behaviors of Dy3+ in the two host materials are discussed systematically. When Dy3+ concentration is greater than 0.07 mol, concentration quenching occurs due to the dipole–dipole interaction. Moreover, the luminescent temperature quenching investigation discloses that the BYGO/BGGO:0.07Dy3+ phosphors have favorable thermostability and resistance to chromaticity shifting. Therefore, the Ba2Ln2Ge4O13-based phosphors would be prospective yellowish-white-emitting fluorescent materials.